2019
DOI: 10.1002/er.5017
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen‐doping activated biomass carbon from tea seed shell for CO 2 capture and supercapacitor

Abstract: Activated carbon is a promising material that has a broad application prospect.In this work, biomass (tea seed shell) was used to prepare activated carbon with KOH activation (referred to as AC), and nitrogen was doped in activated carbon using melamine as the nitrogen source (referred to as NAC-x, where x is the mass ratio of melamine and activated carbon). The obtained activated biomass carbon (activated bio-carbon) samples were characterized by Brunauer-Emmett-Teller (BET)-specific surface area analysis, ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
47
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(49 citation statements)
references
References 45 publications
0
47
1
1
Order By: Relevance
“…The huge SSA, high microporosity, and moderate gravimetric specific capacitance (~200 F g −1 ) of activated carbons can be synthesized by carbonization of a carbon precursor and subsequent physical and/or chemical activation. Quan et al employed tea seed shell as carbon source to produce activated carbon with a SSA of 1503 m 2 g −1 and a capacitance of 168 F g −1 at 0.5 A g −1 by carbonization and KOH activation. KOH is by far the most popular porogen for porous carbon materials.…”
Section: Introductionmentioning
confidence: 99%
“…The huge SSA, high microporosity, and moderate gravimetric specific capacitance (~200 F g −1 ) of activated carbons can be synthesized by carbonization of a carbon precursor and subsequent physical and/or chemical activation. Quan et al employed tea seed shell as carbon source to produce activated carbon with a SSA of 1503 m 2 g −1 and a capacitance of 168 F g −1 at 0.5 A g −1 by carbonization and KOH activation. KOH is by far the most popular porogen for porous carbon materials.…”
Section: Introductionmentioning
confidence: 99%
“…Their results suggest that the sample at 600°C have relatively high nitrogen content and performed a suitable CO 2 capture capacity of 4.4 mmol/g at 298 K under1 bar. Quan et al prepared N‐doped activated carbon by tea seed shell for CO 2 capture, the results concluded that the carbon materials has the highest CO 2 capture capacity of 3.15 mmol/g. Gao et al synthesized CaO‐based adsorbent for CO 2 capture and the CO 2 capture capacity up to 15.1 mmol/g and maintained great cyclic stability.…”
Section: Introductionmentioning
confidence: 99%
“…Rather than the biomass waste, solid waste can be a great option, as this approach could avoid the waste accumulation and also provide an effective alternative to commercialization 9,10 . Due to low cost, low generation of energy, and environmentally friendliness, these materials can be significant to reduce the dependency on high‐cost precursors 11,12 . Deriving activated carbon from the solid waste can be a solution to the combating global waste disposal issues 13,14 …”
Section: Introductionmentioning
confidence: 99%
“…9,10 Due to low cost, low generation of energy, and environmentally friendliness, these materials can be significant to reduce the dependency on high-cost precursors. 11,12 Deriving activated carbon from the solid waste can be a solution to the combating global waste disposal issues. 13,14 On the other hand, due to over dependency on the fossil fuels such as coal for energy demand, we are witnessing the more environmental-related issues such as increasing CO 2 concentration.…”
Section: Introductionmentioning
confidence: 99%